Epidemiology of pediatric dengue virus infection, Scenario from a tertiary level hospital in Bangladesh - Kinkar Ghosh; Selim Reza Tony; Khaleda Islam; Reaz Mobarak; Md. Jahangir Alam; Md. Kamruzzaman; Sumaira Alam; Muhammad Talha; Abdullah Al Faisal; Nahidul Islam; Md Mobarok Hossain; Mst. Noorjahan Begum; et al. (Journal of Infection and Public Health)
Background: Dengue fever is the most rapidly spreading mosquito-borne disease and has grown to be a major public health issue, especially in tropical nations like Bangladesh. Globally, children, adolescents, and young adults bear the largest burden of Dengue; the infection rate is highest among infants. However, the epidemiology of pediatric dengue virus infection has been poorly explored in Bangladesh. Materials and methods: This study was carried out at the Bangladesh Shishu Hospital & Institute from July to October 2023. Among 1102 admitted patients, 722 who were positive for dengue rapid test were enrolled. Results: The highest number of positive patients were 1–5 years old (38 %) followed by 5–10 years (32 %). Vomiting (49 %) was most common after fever (100 %). 71 % of patients showed warning signs, with 17 deaths. All patients received antibiotics, and the number of different antibiotics increased with hospital stay. Real-time RT-PCR was conducted on purposively selected 104 rapid test positives and 50 negatives for serotyping. DENV-2 was the most predominant serotype (80 %), followed by DENV-3 (20 %). Conclusion: This study underscored the need for targeted public health interventions, especially for children with warning signs, to address the high burden of pediatric dengue infection in Bangladesh.